POSTNATAL MORPHOGENESIS OF REPRODUCTIVE ORGANS AND ADRENAL GLAND OF CHICKEN IN EGG DIRECTION - Rakhmanova , Gulnoza Shukhratovna; Dilmurodov , Nasriddin Babakulovich; Fedotov , Dmitry Nikolayevich (Innovative Development in Educational Activities, 2023)
The article analyzes the scientific literature on the postnatal morphogenesis of the reproductive organs and adrenal glands of laying hens. The conclusion about the purposes of research works is given.